Development of a Three-Tier Chemical Equilibrium Multiple-Choice Test to Assess Higher-Order Thinking Skills Based on Brookhart’s Categories - Fauziyah, Neneng; Feronika, Tonih; Yunita, Luki (Journal of Educational Chemistry (JEC), 2024)
This study aimed to develop and validate the Three-Tier Chemical Equilibrium Multiple-Choice Test–HOTS (TTCEMCT–HOTS) instrument. The method employed in this study was Research and Development (R&D) based on Brookhart’s (2010) indicators of higher-order thinking skills. The development procedure began with a preliminary study, followed by product draft planning and product development. These stages were succeeded by an empirical analysis of the TTCEMCT–HOTS to determine the test instrument’s validity, reliability, difficulty level, and discriminating power. The TTCEMCT–HOTS instrument was implemented with Class XI students of SMAN 4 in South Tangerang City. The results of the study were as follows: (1) the developed TTCEMCT–HOTS instrument met the criteria of 32 valid questions, with a reliability coefficient of 0.82 in the “very high” category, a “moderate” difficulty level, and “good” discriminating power; (2) 46.42% of students could solve HOTS questions, while 53.58% could not; (3) the TTCEMCT–HOTS instrument received a positive response from 80.6% of participants, placing it in the “good” category. This study is expected to provide an alternative method for measuring students' higher-order thinking skills using a three-tier test instrument integrated with HOTS indicators.